Monitoring and diagnostics of the quality of scientific and methodological work in the context of competence approach in higher pedagogical education - Степанець, І. О. (Scientific notes of the pedagogical department, 2020)
The article is devoted to the problem of monitoring scientific and methodological work in institutions of higher pedagogical education, in particular to the question of diagnostics of its quality in the context of the of the competence approach. The terminolog ical field of research is defined, the main purpose and tasks of creation of the monitoring system of scientific and methodological work in pedagogical institutions of higher education are outlined. Some features of monitoring research in the field of higher pedagogical education are characterized on the basis of consideration of the origin and development of the “monitoring” phenomenon, its classification, the identification of common and distinguishing features in definitions by diﬀerent authors. Pedagogical diagnostics is considered as a factor in the development of scientific and methodological work, the elements of the model, directions of implementation and stages of diagnostic examination of various aspects of scientific and methodical work realization are named, and its results are predicted. On the basis of the results of scientific generalization, analysis of scientific and methodological work practice in pedagogical institutions of higher education, the key criteria of its quality are identified and the relationship of professional as well as scientific and methodological competence is established. The contradictions that determine the implementation and the main categories of competency approach, the place of scientific and methodological competence in the system of competences of the teacher of a pedagogical institution of higher education are determined. The connection of the process of forming the scientific and methodological competence of the teacher with the innovativeness of his activity at certain stages was fixed. The components of scientific and methodological competence structure are distinguished: epistemological, axiological, traseological, professional and personal. In the context of the conducted research, the object and indicators of the scientific and methodological competence formation of the teacher of a pedagogical institution of higher education were determined, the scheme of its formation was developed and the characteristics of individual levels were drawn up.